Impact of programme versus project aid on economic growth in Sub Sahara Africa - RUGARE, ENIA DAMBUDZO (KDI School, 2016)
As the ongoing debate on aid effectiveness takes a new trail of assessing the efficiency of aid in a disaggregated manner rather than aggregate aid as done in the past, this study seeks to compare how aid delivery modalities affect economic growth. The study analyses the relative effectiveness of programme and project aid effectiveness in promoting economic growth in the Sub Sahara Africa region, one of the world’s poorest region, yet claimed to be the leading beneficiary of foreign aid. Programme aid is allegedly more effective in promoting growth and poverty reduction than project aid since it entails the building of local capacity as well as, strong partnerships between donors and recipient countries. Project aid is blamed for aid fragmentation, and misalignment of aid funded activities with national priorities. To prove the better modality for aid effectiveness, two growth models are estimated using panel data from 41 Sub Sahara African countries for the period 2005 to 2014. In the first model, total aid is disaggregated into programme and project aid variables to see how they relate with growth, and in the second model the aid variables are interacted with policy to see how policy affects their effectiveness on growth. The findings show that indeed programme aid is effective in promoting growth in the Sub Sahara region, though it has diminishing marginal returns on growth. Project aid is shown to have no effect on growth on its own, but will positively affect growth in good policy environments as shown by the positive marginal effect of project aid on growth when it is interacted by policy. The study concludes with a discussion on the application of programme aid and policy recommendations for aid effectiveness in Sub Sahara Africa.
Thesis(Master) --KDI School:Master of Development Policy,2016